Designing Business Models for Sustainable Mass Customization: A Framework Proposal - Hora, Maike; Hankammer, Stephan; Canetta, Luca; Kaygın Sel, Sultan; Gomez, Shirin; Gahrens, Stefan (International Journal of Industrial Engineering and Management, 2016)
In the last three decades, the idea of mass customization has been broadly discussed in management literature as a business model for companies that offer goods to customers with heterogeneous needs. At the same time, the discussion on business models that deal with the increasing customer demand for more sustainable products has gained importance. In the research field of mass customization, there is a lack of research that integrates the new affordances of sustainability into mass customization based business models. With our study, we contribute to this research gap by developing a set of generic sustainable mass customization business model patterns. For this purpose, we first describe the enablers for mass customization and for environmental sustainability separately. In a second step, we combine both perspectives and propose a set of seven generic patterns that serve as guidance for integrating sustainable mass customization on a business model level. Finally, we provide an application of our framework to the Consumer Electronics industry showcasing ideas for practical implementation. Article history: Received (03.11.2016); Revised (22.11.2016); Accepted (19.12.2016)